PERANCANGAN ‘SIGN SYSTEM’ AREA OBJEK WISATA PANTAI PADANG - Geno Maulana, Drs. Ir. Heldi, M.Si., Ph.D., Drs. Ariusmedi, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The Lacks of information about facilities and tourist attractions in Pantai Padang as a Tourism Object makes some visitors confused. The need for a marking system (sign system) in the Pantai Padang areas will make it easier for visitors to get information. The designing of sign systems in the area Object Tourism of Pantai Padang that is interesting, effective and communicative will be the right solution. The purpose of the designer was that the sign system can be built and applied to the Object Tourism of Padang Beach.The design method used was the glass-box by interview and documentation. Completing the analysis used in the progress was 5W + 1H. What is the solution (What), why should design the sign system (Why), who is the target of design (Who), where is the location of the sign system (Where), when the system sign will investigate (When), how to design the sign system (How) . The main media for the announcement was the sign systems. The supporting media for the main design were bus stickers, umbrellas, hats, T-shirts, mugs, stickers and key chains.Keywords: Sign System, Information, Communication, Padang Beach Tourism Object